A new chemical amplification resist system based on novolac and t-BOC protected phosphazene as a dissolution inhibitor - Ahn, K.-D.; Kang, J.-H.; Kim, S.-J.; Park, B.-S.; Park, C.-E.; Park, C.-G. (1992)
t-BOC protected hexakis(4-t-BOC-phenoxy)cyclotriphosphazene, TBP, was synthesized from a semiinorganic phosphazene compound and its acid-catalyzed thermal deprotection was utilized in the design of a three-component positive resist system based on the combined principles of chemical amplification and dissolution inhibition. The new resist system, PTPNS(NR/TBP/PAG), is formulated with novolac resin (NR), TBP and a photoacid generator (PAG). The dissolution characteristics of PTPNS in alkaline development are ideally suited for application to positive type resists which are based on a dissolution inhibition mechanism. The t-BOC protected TBP of the PTPNS resist system effectively acts as an acid-labile dissolution inhibitor of novolac resin when TBP concentration is more than 10 % by weight. As a representative, PTPNS(100/15/5) (by weight parts) exhibited high sensitivity in the range of 20 to 25 mJ/cm2 with contrast of 5 after exposure at 250nm light and PEB treatment at 100 to 130°C. Appropriately formulated PTPNS resist rendered positive-tone patterns down to sub-half micron with high sensitivity when the resist was exposed to KrF excimer laser or electron beam and developed with 2.38 wt% tetramethylamonium hydroxide solution. ？ 1992, The Society of Photopolymer Science and Technology(SPST). All rights reserved.